PENAHANAN PELAKU TINDAK PIDANA DI BAWAH UMUR OLEH PENYIDIK DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 3 TAHUN 1997 TENTANG PENGADILAN ANAK - Adi Sujarwo; Endeh Suhartini; Ju naidi (JURNAL HUKUM DE'RECHTSSTAAT, 2016)
Delinquency problem is the actual problem, in almost all the countries in the world, including Indonesia . Attention to this issue has a lot of thought poured out, either in the form of discussions and seminars which have been held by organizations or government agencies that close relationship with this problem. In a legal perspective, the problem of theft is a criminal act (delict) plaguing the society , in Article 362 Code of Criminal Law of the theft said, " Whoever took the goods wholly or partially belongs to another person , with intent to have unlawful , punishable due to theft, with a maximum imprisonment of 5 ( five ) years or a fine of nine hundred dollars. However, the rules of Article 362 Book of the Law of Criminal Law of the theft and criminal application against minors regulated in Article 26 paragraph (1), 27 and 28, paragraph (1) of Act No. 3 of 1997 on Juvenile Justice , stipulates that the maximum legal threats meted out to convicted child is ½ of the maximum threat of criminal provisions will apply. This study uses a normative approach , in that the data from the literature and from the field as input and information in order to obtain an answer. The results of this research that the detention of offenders under the age of 3 was associated with the Law No. 1997 on the Juvenile Justice conducted an investigation into juvenile delinquents by the investigator children who have an interest, attention, dedication and understanding the problem child. Legal protection of the child as a criminal in the process of investigation has not been in accordance with Law No. 3 of 1997 on Juvenile Justice. Police to interrogate suspected child should distinguish processes and work systems of the investigation and adult actors. Status of child offenders under the custody process by investigators in Bogor City Police Detention by the investigator or prosecutor young child or children with the determination of the judge, in a case and in the manner provided for in the law No.11 of 2012 and the Criminal Procedure Code, determine that the suspect or the accused may be detained. Because there is the term "may" be detained, the detention of children is not always meant to do, so in this case the investigator expected to strongly consider if the detention of children. According to Article 21 paragraph (1) Criminal Code